Um estudo Q sobre a ansiedade na aprendizagem de língua inglesa - Thereza Júnior, Alcides Hermes (2011)
Our study shows opinions of a group of 44 students upon anxiety in the English learning process. The age of participants varied from 18 to 55 years old and they were attending basic, intermediate and advanced lessons. The learners showed their views concerning the affective variable anxiety by rank ordering a 57-statement sample, Q-sample. The sample is part of a data-gathering tool used in Q-Methodology, which is appropriate to investigate human subjectivity. This research approach is considered both a quantitative and qualitative due to the fact that a statistical program computes the data so that the researcher can then analyze and make judgments about them. The Q-sorting allows participants to model their points of views upon the regarding theme being investigated by sorting the statements of the Q-sample. In order to factor analyze the data, we used the PQMethod package. The package data analysis indicated the emergence of 3 groups or factors. The participants in each group shared points of view and rank-ordered statements in similar ways. Once the most important statements for each group were analyzed, we came to the conclusion that some participants had a high sense of group, that alleviated the feeling of anxiety, The Goodfellas, had a positive attitude towards the feeling of anxiety in the language learning process, The Easyriders, and that in specific moments or classroom situations or activities feel uncomfortable and anxious, The caring ones.